2022
DOI: 10.1001/jamanetworkopen.2021.48721
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Germline Sequence Variations Among Patients With Pancreatic Cancer in China

Abstract: IMPORTANCE A higher incidence of pancreatic cancer has been reported in the Chinese population compared with the White population, but genetic differences are unknown to date. Large-sample germline testing for both familial and sporadic pancreatic cancers has been conducted predominantly in White populations, whereas similar studies in Chinese populations are limited. OBJECTIVETo assess the prevalence of germline sequence variations in patients with pancreatic diseases in China. DESIGN, SETTING, AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…Despite recent advances in surgery, chemotherapy, and targeted therapy, the 5-year survival rate of pancreatic cancer patients is only 9% [1,2]. Approximately 80% of patients are not diagnosed until an advanced stage, which limits treatment options [3]. Terefore, the identifcation of diagnostic and prognostic biomarkers is crucial for patients with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in surgery, chemotherapy, and targeted therapy, the 5-year survival rate of pancreatic cancer patients is only 9% [1,2]. Approximately 80% of patients are not diagnosed until an advanced stage, which limits treatment options [3]. Terefore, the identifcation of diagnostic and prognostic biomarkers is crucial for patients with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PALB2 PGVs were statistically more frequent in Chinese patients than in American patients ( p < 0.01), while ATM PGVs showed the opposite trend (Figure 3D). Interestingly, a recent study also showed that PALB2 PGVs were more prevalent in a Chinese PDAC cohort than in an American PDAC cohort from the Johns Hopkins Hospital (6/1009 [0.6%] vs. 2/854 [0.2%]), although the difference was not statistically significant 11 …”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, a recent study also showed that PALB2 PGVs were more prevalent in a Chinese PDAC cohort than in an American PDAC cohort from the Johns Hopkins Hospital (6/1009 [0.6%] vs. 2/854 [0.2%]), although the difference was not statistically significant. 11 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Large cohort studies like TCGA (The Cancer Genome Atlas) revealed the complex somatic molecular landscape of pancreatic cancer and paved the way for precision medicine. 2 For studies in Chinese population, our previous work 3 summarized the germline mutations in 1009 pancreatic cancer patients and performed comparative analysis with cohorts of other races. We found that pathogenic sequence variations were detected in 6.2% of patients with PDAC.…”
mentioning
confidence: 99%